2016
DOI: 10.1111/mec.13934
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation effects of ciprofloxacin and sulphamethoxazole in Microcystis aeruginosa and isobaric tag for relative and absolute quantitation‐based screening of antibiotic targets

Abstract: Antibiotics are normally regarded as safe to aquatic ecosystems when their contamination concentrations are lower than the toxic threshold. This study observed the hazard of ciprofloxacin, sulphamethoxazole and their binary mixture to the aquatic environment at environmentally relevant concentrations lower than the toxic threshold, due to the stimulation on the bloom of Microcystis aeruginosa. The enhanced growth of M. aeruginosa, coupled with elevated photosynthesis activity, was exerted by 50-200 ng/L of cip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…In another study, amoxicillin at 200–500 ng/L did not alter or slightly enhanced the growth of Microcystis aeruginosa , and the stimulatory effect was correlated with the increase in N concentration (from 0.05 to 5 mg/L) in the growth medium [211]. Moreover, growth of Microcystis aeruginosa was improved by up to 33% in the presence of 50–200 ng/L of ciprofloxacin [212] and by up to 25% in the presence of 100–200 ng/L of sulphamethoxazole [212]. Interestingly, the cyanobacterium Phormidium valderianum was able to utilize ampicillin as a nitrogen source via extracellular production of β-lactamase, the enzyme that breaks a β-lactam ring [213].…”
Section: Stimulatory Effect Of Phrs On Microalgal Growthmentioning
confidence: 99%
“…In another study, amoxicillin at 200–500 ng/L did not alter or slightly enhanced the growth of Microcystis aeruginosa , and the stimulatory effect was correlated with the increase in N concentration (from 0.05 to 5 mg/L) in the growth medium [211]. Moreover, growth of Microcystis aeruginosa was improved by up to 33% in the presence of 50–200 ng/L of ciprofloxacin [212] and by up to 25% in the presence of 100–200 ng/L of sulphamethoxazole [212]. Interestingly, the cyanobacterium Phormidium valderianum was able to utilize ampicillin as a nitrogen source via extracellular production of β-lactamase, the enzyme that breaks a β-lactam ring [213].…”
Section: Stimulatory Effect Of Phrs On Microalgal Growthmentioning
confidence: 99%
“…However, four of the target antibiotics, amoxicillin, spiramycin, ciprofloxacin, and sulfamethoxazole, were indicated to regulate the expression of ATP‐binding cassette transporters and facilitate the export/secretion of cellular and exogenous substances (Liu et al. ). The presence of coexisting antibiotics may promote the secretion of H 2 O 2 and glyphosate from cyanobacterial cells and alleviate stress in the antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 100 lg Á L À1 ofloxacin was found to increase the chlorophyll a content and the photosynthetic activity of Microcystis aeruginosa (Deng et al 2015). In addition, 0.001-0.1 lg Á L À1 erythromycin was observed to stimulate the growth and photosynthetic activity of Microcystis flos-aquae (Wan et al 2015, Liu et al 2017. Previous studies by our group found that spiramycin, amoxicillin, ciprofloxacin, and sulfamethoxazole each stimulated the photosynthesis, growth, and production of microcystins (MCs) in M. aeruginosa (Liu et al , 2017.…”
mentioning
confidence: 98%
See 2 more Smart Citations